The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jfpp.15572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical, rheological, microstructural, and microbial characteristics of synbiotic ultrafiltrated white cheese treated with transglutaminase

Abstract: Functional foods are part of a daily diet that, in addition to basic nutritional properties, have an effect beyond nutritional value on community health (Rivera-Espinoza & Gallardo-Navarro, 2010).Probiotic food products are the main and the most important functional foods which comprise about 70 percent of these products (Granato et al., 2010). Production of probiotics foods with sufficient amounts of live microorganisms at the time of consumption is very important issue. Many factors affect the survival of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…These micrographs show that the cheese samples treated with TGase displayed more compact and dense protein network with less voids (Figure 4d–i), compared with that of control cheese (without TGase), which showed open and porous structure with larger void sizes (Figure 4a–c). In a recent study, Torabi and Jooyandeh (2021) reported that probiotic ultrafiltered white cheese treated by TGase had a more compact and less porous protein structure than control cheese without TGase.…”
Section: Resultsmentioning
confidence: 99%
“…These micrographs show that the cheese samples treated with TGase displayed more compact and dense protein network with less voids (Figure 4d–i), compared with that of control cheese (without TGase), which showed open and porous structure with larger void sizes (Figure 4a–c). In a recent study, Torabi and Jooyandeh (2021) reported that probiotic ultrafiltered white cheese treated by TGase had a more compact and less porous protein structure than control cheese without TGase.…”
Section: Resultsmentioning
confidence: 99%
“…The count of L. acidophilus LA5 was evaluated through the serial dilution technique and using the pour plate technique. One‐milliliter aliquots from each yogurt sample were successively diluted with peptone water (0.1%) and 10 −5 –10 −7 dilutions were cultured on MRS agar containing 0.15% bile salts (Torabi et al., 2021 ). After incubation at 37°C for 72 h, the viability of probiotics in the plates (with 25–250 colonies) was recorded and expressed in log cfu/g.…”
Section: Methodsmentioning
confidence: 99%
“…Yogurt is a source of bioactive peptides which are developed throughout the process of fermentation. In addition, yogurt contains other health‐promoting components such as beneficial lactic acid bacteria (LAB) specifically probiotics that are beneficial to the function of human gut microbiota (Torabi et al., 2021 ). Probiotics are living microorganisms that confer a health advantage to the host when consumed in adequate amounts (Hill et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sample with an enzyme ratio of 5 U/g protein was relatively close to the control sample (p>0.05), a significantly higher value was found for the sample with an mTG ratio of 2 U/g protein (p<0.05). The mTG enzyme cross-links proteins in the cheese network and forms isopeptide bonds (Torabi et al, 2021). Accordingly, the cheese texture becomes more compact and harder (Oezer et al, 2013).…”
Section: Texture Profile Analysis 295mentioning
confidence: 99%